2016
DOI: 10.1002/2016jd024758
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the East Asian Monsoon on springtime dust concentrations over China

Abstract: We use 150 year preindustrial simulations of the Community Earth System Model to quantify the impacts of the East Asian Monsoon strength on interannual variations of springtime dust concentrations over China. The simulated interannual variations in March‐April‐May (MAM) dust column concentrations range between 20–40% and 10–60% over eastern and western China, respectively. The dust concentrations over eastern China correlate negatively with the East Asian Monsoon (EAM) index, which represents the strength of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 92 publications
(132 reference statements)
2
28
0
Order By: Relevance
“…At present, due to the limitations of the observations and model capability, we could not give a quantitative assessment of the influences of La Niña events on natural aerosols. A recent work reported that the variation of EASM has a significant impact on the dust concentrations over eastern China and highlighted the role of atmospheric circulation for natural aerosols [ Lou et al ., ]. On this point, the possible influences of ENSO on the natural aerosols deserve further consideration…”
Section: Summary and Discussionmentioning
confidence: 99%
“…At present, due to the limitations of the observations and model capability, we could not give a quantitative assessment of the influences of La Niña events on natural aerosols. A recent work reported that the variation of EASM has a significant impact on the dust concentrations over eastern China and highlighted the role of atmospheric circulation for natural aerosols [ Lou et al ., ]. On this point, the possible influences of ENSO on the natural aerosols deserve further consideration…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The dust aerosol increases and decreases over the TP as the index weakens and enhances, respectively. Lou et al (2016) also demonstrated a clear negative correlation between the EASM and the dust concentration over eastern China in spring. Based on the variation in the column dust load shown in …”
Section: Relationship Between the Easm And Dust Loading Over The Tpmentioning
confidence: 80%
“…Aerosols, including dust aerosols, have been shown to affect the intensity of the EASM and variations in the EASM can modulate the spatiotemporal distribution of dust aerosols in East Asia. A recent modeling study by Lou et al (2016) indicated that there was a negative correlation between the spring dust loading in eastern China and the East Asian monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, East Asia experiences significant monsoon events that are characterized by cold and dry air in winter with northwesterly winds in the lower troposphere and hot and wet air in summer with the reverse winds [ Yang et al ., ]. The effects of the East Asian Monsoon system on dust aerosols has been investigated by a number of previous measurement and modeling studies [ Wu et al ., ; Sun and Liu , ; Lou et al ., ].…”
Section: Introductionmentioning
confidence: 98%
“…This study expands on the work of Lou et al . [], who used CESM to investigate the impacts of the East Asian Monsoon on dust concentrations and its direct radiative forcing in spring and suggested that interannual variations in dust emissions enhance the impact of the East Asian Monsoon on net RF over eastern China by about 40%. However, they did not investigate the impacts of changes in dust emissions on the temperature and precipitation in the region, which is the focus of this study.…”
Section: Introductionmentioning
confidence: 99%